Hybridization of Concentrated Solar Thermal, Geothermal, and Biomass: Case Study on Kizildere-2 Geothermal Power Plant - Bertug Celebi; Shahab Rohani; Pınar Derin-Güre; Nicholas Chandler; Tuğrul Hazar; Ural Halaçoğlu; Derek Baker (Energies)
The usage of fossil fuel in the energy sector is the primary factor for global GHG emissions, so it is crucial to better utilize RE sources. One way to do that is to hybridize RE technologies to make up for their deficiencies while enabling a more synergistic power production. This study utilizes such an approach to hybridize the KZD-2 Geothermal Power Plant (GPP) with CST and biomass in the southwest region of Turkiye. The main motivation is to address the two main issues of GPPs—excess turbine capacities happening over the operating years and decreasing performance during hot summer months—while also increasing the flexibility of KZD-2. A topping cycle of CST–biomass is added utilizing a PTC field as the CST technology and olive residual biomass combustion as the biomass technology. The hybrid plant is simulated on TRNSYS, and the energetic data show that it is possible to generate more than 20 MWe of additional power during sunny and clear sky conditions while also increasing the Capacity Factor (CF) from 69% to 74–76%. Moreover, the financial results show that the resulting LCOAE is 81.19 USD/MWh, and the payback period is five or nine years for using the YEKDEM incentive or the spot market prices, respectively.